Analysis of Student Self-Confidence at SMAN 2 Ranah Pesisir in the New Normal Era - Hayadi, Muslim; Netrawati, Netrawati (Current Issues in Counseling, 2022)
Confidence is one aspect of personality that functions to encourage students to achieve success in learning. The self-confidence that an individual has can be a benchmark for how the individual displays his abilities, talents and competencies. This study aims to determine the level of student confidence in learning in the new normal era at SMAN 2 Ranah Pesisir. The type of research used is a descriptive quantitative approach. The population is all students of SMAN 2 Ranah Pesisir with a total of 214 students and a sample of 139 students. The sampling technique used is stratified random sampling. The research instrument uses a self-confidence questionnaire which is described by each indicator of self-confidence. Data analysis technique using descriptive analysis. Based on the results of the study, it was described that the self-confidence of students at SMAN 2 Ranah Pesisir in the new normal era was in the high category. This illustrates that the students at SMAN 2 Ranah Pesisir are mostly confident in their abilities and are able to make appropriate and effective decisions and actions in the learning process. This is in line with the opinion that self-confidence is an individual's ability to take appropriate and effective actions in any situation, even in challenging situations.